Relationship Between Postnatal Mothers' Knowledge And Care Behavior Of The Umbilical Cord In Newborns In The Working Area Of The Kepenuhan Community Health Center - Sri Wulandari; Sulistiyawati; Yuyun Beweli Fahmi; Elvira Junita (CV. AFDIFAL MAJU BERKAH, 2025)
Proper umbilical cord care is essential to prevent infections in newborns, and a mother’s knowledge and behavior are crucial factors influencing this practice. This study aimed to determine the relationship between postpartum mothers’ knowledge and their umbilical cord care behavior in newborns at the Kepenuhan Community Health Center. A quantitative method with a cross-sectional design was used. The study employed a total sampling technique, including all 30 postpartum mothers in the population. Data were collected using a 30-question questionnaire and analyzed with univariate and bivariate analysis, specifically the Chi-Square test. The findings revealed that the majority of mothers had good knowledge (66.7%), and 50% demonstrated good care behavior. The Chi-Square test result (p=0.020) indicated a significant relationship between knowledge and care behavior. The study concludes that there is a positive association between a mother’s knowledge and her behavior in umbilical cord care, suggesting that increased awareness can directly improve neonatal health outcomes. The results highlight the importance of targeted health education, particularly during antenatal and postnatal visits, to ensure that mothers receive accurate information and practical guidance. Strengthening the role of healthcare workers, especially midwives, in providing consistent counseling and demonstrations is recommended. Furthermore, the findings can serve as a basis for health centers to design community-based interventions that involve families in newborn care. By enhancing maternal knowledge and skills, preventable neonatal infections can be reduced, thereby supporting broader efforts to lower infant morbidity and mortality rates.